Pengembangan Profesi Guru dalam Meningkatkan Kinerja Guru SDN 007 Sei Beduk Kota Batam - Kartawinata Kartawinata (Journal on Education, 2023)
Study this aim for know description about development teaching profession , for know description level teacher performance, and for know influence development teaching profession to teacher performance The essence of the study focused on influencing factors teacher performance , as for factors studied in study this is development teacher profession . Method research used is survey method . Data collection techniques performed in study this use questionnaire . Respondents in study this are teachers at SDN 007 Sei Beduk in Batam City , with a total of 18 teachers. Data analysis techniques using regression simple. Research results this show : (1) development the teaching profession is in category enough effective, and teacher performance is in the category enough height ; (2) development influential teaching profession positive to performance